All Days 2011
DOI: 10.2118/150515-ms
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Thermal and Carbon Dioxide Recovery Methods beyond their Conventional Limits: Downhole Innovation

Abstract: Steam or CO 2 injection methods account for most of the oil recovered worldwide with Enhanced Oil Recovery (EOR) methods. Currently heavy oil production is less than 7% of the world's oil production; this percentage is not expected to increase dramatically without significant changes in reservoir management. Steam and CO 2 have been used successfully since early 1960s --steam in viscous heavy oils and CO 2 mostly in pressurized light oil fields but also in some heavy oil fields. What limits a wider application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…20 Furthermore, produced flue gas can move faster than steam as it does not need to preheat the reservoir to provide the circumstances for gas dissolution in heavy oil. 20 So, flue gas can deliver a massive amount of energy during the injection process at lower temperatures, which was comprehensively discussed by Capper et al 21 Monte-Mor et al 22 developed a set of experiments to evaluate the effectiveness of produced flue gas by down hole steam generators coupled with the dynamic steam injection to recover heavy oil (16.14°API) from sand pack, representing the sandstone reservoirs. They observed that flue gas and steam coinjection can reduce the steam volume (10% less steam) more than steam-only injection to produce the same amount of crude oil.…”
Section: Flue Gas Injection Typesmentioning
confidence: 99%
“…20 Furthermore, produced flue gas can move faster than steam as it does not need to preheat the reservoir to provide the circumstances for gas dissolution in heavy oil. 20 So, flue gas can deliver a massive amount of energy during the injection process at lower temperatures, which was comprehensively discussed by Capper et al 21 Monte-Mor et al 22 developed a set of experiments to evaluate the effectiveness of produced flue gas by down hole steam generators coupled with the dynamic steam injection to recover heavy oil (16.14°API) from sand pack, representing the sandstone reservoirs. They observed that flue gas and steam coinjection can reduce the steam volume (10% less steam) more than steam-only injection to produce the same amount of crude oil.…”
Section: Flue Gas Injection Typesmentioning
confidence: 99%
“…La combinación de vapor y gases de combustión modifica el perfil de inyección, ya que a medida que se disuelve y difunde el CO 2 en el crudo, el vapor tendrá un mayor radio de calentamiento. [3,11,12] Si el CO 2 no alcanza la PMM se comportará de forma inmiscible, al igual que el N 2 , que tiene presiones mínimas de miscibilidad elevadas (superiores a los 5.000psi [13]), En condiciones inmiscibles existe recuperación de aceite por hinchazón y vaporización limitada del gas; no obstante, el mecanismo predominante es de desplazamiento por empuje.…”
Section: Gases De Combustiónunclassified
“…Four common recovery methods involving thermal injection are: in situ combustion (ISC); cyclic steam stimulation (huff and puff/ CSS); steam-assisted gravity drainage (SAGD) and high pressure air injection (HPAI). Figure 11 shows schematically the ISC, which employs the injection of air to ignite the small fraction of oil, generates heat internally, and produces the combustion gases to enhance the oil recovery especially for heavy oil sandstone reservoirs (Yazdani and Maini 2005;Alvarado and Manrique 2010;Capper et al 2011;Knorr and Imran, 2011). Figure 12 shows schematically the CSS.…”
Section: Thermal Eormentioning
confidence: 99%